Implementasi Pendekatan Activity Relationship Chart dalam Perancangan Tata Letak Gudang Baru untuk Memperpendek Perpindahan Material di UD. M - Divibriani, Mentari; Herlina, Herlina (Fakultas Teknik Universitas Tulang Bawang, 2025)
This research discusses the issues faced by UD M, which produces crispy brownie chips, where the finished goods warehouse often becomes overcrowded due to production reaching 253 boxes, while the warehouse capacity is only 48 boxes. Due to other factors as well, the owner decided to move all activities, starting from raw material storage, production, and finished goods storage, to another location. The problem is the absence of a layout for the new warehouse. With this issue, the author designed the factory layout based on the Shared Storage method, considering material handling and the FIFO picking system. This research aims to provide the owner of UD M with considerations for arranging the facility layout in the new building. In addition to changing the layout of the finished goods warehouse, the owner plans to relocate the factory. The author reorganized the new factory of UD. M based on the results of the Activity Relationship Chart.(ARC). The research results show that the raw material warehouse, which initially measured 11.30 m², has been reduced to 10.32 m². Then, the finished goods warehouse, which initially could only hold 48 boxes, can now hold up to 123 boxes per day. By changing the layout of the production area, the production flow also becomes more organized and systematic. Keywords: ARC, FIFO, Production Flow, Share Storage, Warehouse